Effects of simulated in vitro gastrointestinal digestion on antioxidant activities and potential bioaccessibility of phenolic compounds from K. coccinea fruits - Luo, Xiaochen; Tian, Miaomiao; Cheng, Yingying; Ji, Caizhe; Hu, Shende; Liu, Hongnan; Lu, Jun; Ren, Jiali (Frontiers in Nutrition, 2022)
The changes of bioactive substances in peels and sarcocarps of three different varieties of K. coccinea (Dahong, Fenhong and Zihei) were evaluated by in vitro simulation model. The results showed before digestion the highest content of TPC (2.265 ± 0.127 mg GAE/g DW) and the highest content of TFC (10.379 ± 0.093 mg GAE/g DW) were found in Fenhong fruit. The highest release of TPC and TFC after simulated gastric digestion were observed in the Dahong and Zihei sarcocarp, which increased by 98.7% and 20%, respectively. During oral and intestinal digestion, the content of bioactive compounds showed a decreasing trend. The 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging ability, (2,2-azino-bis(3-ethylbenzothiazoline) (ABTS) sulfonic acid free radical scavenging ability, ferric ion reducing antioxidant power (FRAP) results showed that the antioxidant capacity of K. coccinea fruits increased most significantly (26.9%~181%) in gastric digestion stage, and then decreased after intestinal digestion stage. The recoveries of TPC and TFC were all increased after whole simluated digestion, as well as their bioaccessibility in sarcocarps were higher than those in peels, especially for the bioaccessibility of TPC and TFC in Dahong reached to 50.53 % and 48.19 %, respectively. These results indicated that the peel and sarcocarp of K. coccinea had good antioxidant activity, with high bioaccessibility of phenolics could be a promising antioxidants source for food industry.